IMPROVING STUDENTS’ LISTENING COMPREHENSION THROUGH COOPERATIVE LISTENING - Teguh Satria Amin (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2019)
This research attempts to improve the students’ achievement on listening comprehension through cooperative listening. The research was conducted at the second grade by using classroom action research at the second grade students of SMA N 6 Medan. Four classes were selected as subjects that consist of 35 students. The students were taught cooperative listening meanwhile for the qualitative data, interview and observation were conducted. The quantitative data were collected by giving 10 multiple choice tests and calculating the mean. The result of the research shows that the mean of the second cycle (80.85%) was higher than the mean of the first cycle (68.28%). Based on the observation and interview, the students were becoming active and enthusiastic during the teaching learning processes.